1759 metų „Ziwato” negimininiai įvardžiai ir jų raida - Vaičiakauskienė, Sonata (Baltistica, 2004)
NONGENDERED PRONOUNS IN “ZIWATAS” (1759) AND THEIR EVOLUTIONThe following general conclusions can be made after comparison of the declensions of the stems of nongendered pronouns in the “Ziwatas” dialect with modern dialect of Kretinga. Only shortened forms of the dative singular case mun, tau, sau are used consistently in “Ziwatas”. The forms mô̩n and mò̩nęi, tâu and tàvê̩̩i, sâu and sàvê̩̩i are used in the Kretinga dialect nowadays. There are postpositive locative cases of pronouns occasionally used in “Ziwatas”, but they are not authentic. In the north Zemaitian dialect of Kretinga the plural forms mûˑsa, jûˑsa are used. These are created on the basis of the forms of the genitive singular case. The text analyzed here still records the older forms muʃu 278, juʃu 962.
Keywords: lietuvių kalba; senieji raštai; įvardis